2014
DOI: 10.1371/journal.pone.0089532
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Kinetics of Phenotypic Switching in the Arabinose Utilization System of E. coli

Abstract: Inducible switching between phenotypes is a common strategy of bacteria to adapt to fluctuating environments. Here, we analyze the switching kinetics of a paradigmatic inducible system, the arabinose utilization system in E. coli. Using time-lapse fluorescence microscopy of microcolonies in a microfluidic chamber, which permits sudden up- and down-shifts in the inducer arabinose, we characterize the single-cell gene expression dynamics of the araBAD operon responsible for arabinose degradation. While there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 45 publications
(73 reference statements)
1
47
0
Order By: Relevance
“…Both sugar utilization systems exhibit bimodal responses (11)(12)(13)(14)(15)(16), and our initial goal was to understand how catabolite repression affected the response of individual cells. Our data show that the response to the two sugars is multimodal and that the shape of this distribution is determined by the reciprocal regulation of these two sugar utilization systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both sugar utilization systems exhibit bimodal responses (11)(12)(13)(14)(15)(16), and our initial goal was to understand how catabolite repression affected the response of individual cells. Our data show that the response to the two sugars is multimodal and that the shape of this distribution is determined by the reciprocal regulation of these two sugar utilization systems.…”
Section: Discussionmentioning
confidence: 99%
“…Both the arabinose and xylose genes are known to exhibit a bimodal/heterogeneous induction response to their cognate sugar (11)(12)(13)(14)(15)(16). Of particular note, a previous study by Afroz and coworkers investigated the expression of the arabinose and xylose metabolic genes in E. coli in response to their cognate sugar (11).…”
mentioning
confidence: 99%
“…Yet another recent example for heterogeneous expression of genes linked to metabolic traits concerns the arabinose utilization system in E. coli (63,64). With quantitative time-lapse microscopy and by challenging E. coli cells with very low concentrations of arabinose, a time delay in the response of single cells to arabinose was discovered.…”
Section: Metabolic Activities Are Not Always Uniform In Batch Culturesmentioning
confidence: 99%
“…Thus, the design of suitable biosensors would provide a convenient tool for strain analysis and screening, and might be especially useful for the identification of non-intuitive targets for strain improvement (Binder et al 2012;Mahr et al 2015;Mustafi et al 2012). However, our study revealed that several parameters require careful consideration to set up a screening procedure for effector-responsive promoters, including the adaption to growth medium, the uptake and catabolism of effector molecules (Luo et al 2014;Payne 1977), the activation of the gene expression machinery (Bintu et al 2005b;Carey et al 2013;Fritz et al 2014;Mäkelä et al 2013), the maturation of fluorescent proteins (Craggs 2009;Iizuka et al 2011), and last but not least, the composition of the particular growth medium. Here, we used M9 minimal medium due to its lack of other amino acids and carbon source and its very low auto-fluorescence (Miller 1972).…”
Section: Discussionmentioning
confidence: 99%